Bariery i przykłady wsparcia w procesie edukacji w środowisku osób z wadami słuchu - Iwanicka , Beata (Studia Edukacyjne, 2017)
The article presents the problems of deaf and hard of hearing people in education. This topic is widely analyzed. The text describes the difficulties experienced by students at school, at various stages of learning, and the barriers experienced by deaf and hard of hearing students at higher education levels. In general, the hearing deficit entails various communication complications. The person with hearing impairment has a limited opportunity to have different experiences and what is most important in the text – hearing loss or deafness often makes it impossible to gain an optimal education. There are different methods of educating people from the non-hearing environment, depending on the degree of hearing impairment. Hearing impaired student often has difficulty understanding Polish, as it is not always their first language (their first language may be the Polish sign language). Hearing impaired students sometimes don’t understand academic texts because they have weaker poorer vocabulary due to their communication dysfunction. Another issue is the social isolation of many people with hearing impairments which often have a dilemma which environment to integrate with – with hearing or hearing impaired? Teaching staff approaches such people in different ways. Stereotypes do not help in educational progress (for example, the assumption that such students communicate only in sign language). It is important to be aware of the types of hearing loss and the different types of hearing (each hearing impaired hears differently and needs an individual approach). Finally, the article discusses the issue of education of people with hearing impairment from the category of “space”. Through “space” you can understand here the environment (school space, classes and associated architectural-acoustic barriers) as well as the language of the Deaf. The sign language is specifically designed for living space (some of the signatures must be shown in the specified movement and direction, depending on the intention of the sender).